Analisis Nilai-Nilai Kehidupan dan Pembelajaran dalam Novel Janji Karya Tere Liye - Nasyitha Rizqiya (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This article aims to analyze the values of life and learning contained in the novel Janji by Tere Liye. This novel tells the story of the life journey of the main character, Bahar, who undergoes an extraordinary transformation from a troubled teenager to a figure full of good values, thanks to five sacred promises inherited from his teacher. This study uses a qualitative approach with a literature study method, and utilizes the theory of literary sociology to see the relationship between the contents of the novel and social reality. The results of the analysis show that this novel is full of life values such as mutual assistance, honesty, patience, caring, and charity. These values not only shape the character of the character, but are also in line with the five main principles in Strengthening Character Education (PPK), namely religious, nationalistic spirit, independence, cooperation, and integrity. The novel Janji can be used as an effective learning medium in character education because it conveys moral messages emotionally and reflectively. This article recommends the use of literary works as educational sources in classroom learning to shape students with strong character.